Nucleus‐localized 21.5‐kDa myelin basic protein promotes oligodendrocyte proliferation and enhances neurite outgrowth in coculture, unlike the plasma membrane‐associated 18.5‐kDa isoform. Issue 3 (27th November 2012) - Smith, Graham S.T.; Samborska, Bożena; Hawley, Steven P.; Klaiman, Jordan M.; Gillis, Todd E.; Jones, Nina; Boggs, Joan M.; Harauz, George
Abstract The classic myelin basic protein (MBP) family of central nervous system (CNS) myelin arises from transcription start site 3 of the Golli (gene of oligodendrocyte lineage) complex and comprises splice isoforms ranging in nominal molecular mass from 14 kDa to (full‐length) 21.5 kDa. We have determined here a number of distinct functional differences between the major 18.5‐kDa and minor 21.5‐kDa isoforms of classic MBP with respect to oligodendrocyte (OLG) proliferation. We have found that, in contrast to 18.5‐kDa MBP, 21.5‐kDa MBP increases proliferation of early developmental immortalized N19‐OLGs by elevating the levels of phosphorylated ERK1/2 and Akt1 kinases and of ribosomal protein S6. Coculture of N2a neuronal cells with N19‐OLGs transfected with the 21.5‐kDa isoform (or conditioned medium from), but not the 18.5‐kDa isoform, caused the N2a cells to have increased neurite outgrowth and process branching complexity. These roles were dependent on subcellular localization of 21.5‐kDa MBP to the nucleus and on the exon II‐encoded segment, suggesting that the nuclear localization of early minor isoforms of MBP may play a crucial role in regulating and/or initiating myelin and neuronal development in the mammalian CNS. © 2012 Wiley Periodicals, Inc.